Predicting Geriatric Falls Following an Episode of Emergency Department Care: A Systematic Review. (7th October 2014) - Carpenter, Christopher R.; Avidan, Michael S.; Wildes, Tanya; Stark, Susan; Fowler, Susan A.; Lo, Alexander X.; Gerson, Lowell
Abstract Background Falls are the leading cause of traumatic mortality in geriatric adults. Despite recent multispecialty guideline recommendations that advocate for proactive fall prevention protocols in the emergency department (ED), the ability of risk factors or risk stratification instruments to identify subsets of geriatric patients at increased risk for short‐term falls is largely unexplored. Objectives This was a systematic review and meta‐analysis of ED‐based history, physical examination, and fall risk stratification instruments with the primary objective of providing a quantitative estimate for each risk factor's accuracy to predict future falls. A secondary objective was to quantify ED fall risk assessment test and treatment thresholds using derived estimates of sensitivity and specificity. Methods A medical librarian and two emergency physicians (EPs) conducted a medical literature search of PUBMED, EMBASE, CINAHL, CENTRAL, DARE, the Cochrane Registry, and Clinical Trials. Unpublished research was located by a hand search of emergency medicine (EM) research abstracts from national meetings. Inclusion criteria for original studies included ED‐based assessment of pre‐ED or post‐ED fall risk in patients 65 years and older with sufficient detail to reproduce contingency tables for meta‐analysis. Original study authors were contacted for additional details when necessary. The Quality Assessment Tool for Diagnostic Accuracy Studies (QUADAS‐2) was used to assess individual study quality for those studies that met inclusion criteria. When more than one qualitatively similar study assessed the same risk factor for falls at the same interval following an ED evaluation, then meta‐analysis was performed using Meta‐DiSc software. The primary outcomes were sensitivity, specificity, and likelihood ratios for fall risk factors or risk stratification instruments. Secondary outcomes included estimates of test and treatment thresholds using the Pauker method based on accuracy, screening risk, and the projected benefits or harms of fall prevention interventions in the ED. Results A total of 608 unique and potentially relevant studies were identified, but only three met our inclusion criteria. Two studies that included 660 patients assessed 29 risk factors and two risk stratification instruments for falls in geriatric patients in the 6 months following an ED evaluation, while one study of 107 patients assessed the risk of falls in the preceding 12 months. A self‐report of depression was associated with the highest positive likelihood ratio (LR) of 6.55 (95% confidence interval [CI] = 1.41 to 30.48). Six fall predictors were identified in more than one study (past falls, living alone, use of walking aid, depression, cognitive deficit, and more than six medications) and meta‐analysis was performed for these risk factors. One screening instrument was sufficiently accurate to identify a subset of geriatric ED patients at low risk for falls with a negative LR of 0.11 (95% CI = 0.06 to 0.20). The test threshold was 6.6% and the treatment threshold was 27.5%. Conclusions This study demonstrates the paucity of evidence in the literature regarding ED‐based screening for risk of future falls among older adults. The screening tools and individual characteristics identified in this study provide an evidentiary basis on which to develop screening protocols for geriatrics adults in the ED to reduce fall risk